A Systematic Review: Instruments to Measure Educator Retention Concepts. Issue 3 (May 2021) - Tufano, Virginia; Dolan, Diana Martinez; Willson, Pamela
Abstract: AIM: The purpose of this study was to identify quantitative instruments that measure characteristics that support nurse educator education, specifically social support, motivation, and work opportunity. BACKGROUND: Vacancies in nurse faculty positions have left nursing education unable to increase the number of nurses prepared to enter the workforce. METHOD: A review of education, nursing, and psychological databases was undertaken to identify reported instruments. Identified instruments were analyzed to match three framework-derived concept categories: social support, internal motivators, and work opportunity. Search terms, retrievals, and quality assessments are discussed; identified instruments are ranked by concept categories. RESULTS: Of 98 articles retrieved, 85 underwent full review, and 7 met the inclusion criteria. From these reports, 20 unique instruments were identified and analyzed. CONCLUSIONS: There are quantitative instruments that measure the concepts found in the Nurse Educator Retention Framework. Abstract : Supplemental digital content is available in the text.